Comparison of the 7th and 8th edition of American Joint Committee on Cancer (AJCC) staging systems for breast cancer patients: a Surveillance, Epidemiology and End Results (SEER) Analysis - Shao N; Xie C; Shi Y; Ye R; Long J; Shi H; Shan Z; Thompson AM; Lin Y (Cancer Management and Research, 2019)
Nan Shao,1,* Chuanbo Xie,2,* Yawei Shi,1 Runyi Ye,1 Jianting Long,3 Huijuan Shi,4 Zhen Shan,1 Alastair M Thompson,5 Ying Lin1 1Department of Breast Surgery, Breast Disease Center, The First Affiliated Hospital, Sun Yat-sen University, Guangzhou, Guangdong, China; 2Department of Cancer Prevention Research, State Key Laboratory of Oncology in South China, Collaborative Innovation Center for Cancer Medicine, Sun Yat-sen University Cancer Center, Guangzhou, Guangdong, China; 3Department of Medicinal Oncology, The First Affiliated Hospital, Sun Yat-sen University, Guangzhou, Guangdong, China; 4Department of Pathology, The First Affiliated Hospital, Sun Yat-sen University, Guangzhou, Guangdong, China; 5Department of Breast Surgery, Division of Surgical Oncology, Dan L Duncan Comprehensive Cancer, Baylor College of Medicine, Houston, TX, USA *These authors contributed equally to this work Background: The 8th edition of the American Joint Committee on Cancer (AJCC) staging system for breast cancer has incorporated tumor grade, estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2 status as staging biologic factors reflecting prognosis. The purpose of this study was to compare the 7th and 8th edition of AJCC staging system for prognostic impact. Materials and methods: Primary breast cancer patients diagnosed from 2010 to 2014 were identified using the Surveillance, Epidemiology and End Results 18 registries research database. Breast cancer-specific survival (BCSS) and overall survival (OS) between stages were estimated using the Kaplan–Meier method and compared using the log-rank test. Multivariable analysis was performed using Cox proportional hazards regression analysis to identify factors independently associated with outcome. Akaike’s information criterion (AIC) was calculated to estimate how well the staging system fitted the data and the complexity of the model. Results: A total of 184,221 primary breast cancer patients were identified in the 7th AJCC staging system; 16,145 (8.8%) patients could not be categorized according to 8th AJCC prognostic staging system leaving 168,076 patients included for final analyses. The 8th AJCC performed well with the BCSS and OS concordant with stage. A total of 89,494 (53.2%) of patients were restaged to a different stage group in the 8th AJCC; stage IIIA in the 7th AJCC migrated to stage IB with a worse prognosis than IIA and IIB in the 8th AJCC. Nevertheless, the 8th AJCC had a better AIC than the 7th staging system. Conclusion: The prognostic accuracy of the 8th AJCC staging system was generally superior to the 7th AJCC, although subtle differences between the two systems should be noted in comparative studies. Keywords: breast cancer, prognosis, AJCC